Zoonosis as a public health problem from a comprehensive vision (Revista Venezolana de Salud Pública, 2020)
Zoonoses as the result of a process where various factors intervene and are related to epidemiological, economic and social variables, this article reviewing the was developed, with the aim of reflecting on the contextualization of the control programs of the Zoonosis as a public health problem, for the reflexive argumentation of this document, a documentary review was carried out, with extraction, compilation of information, and analysis of the theoretical foundations and the results presented in the consulted investigations, visualizing the criteria described by different authors, which can be of great contribution due to the little information on communicable diseases from animals to humans and the actions of INSAI, as the governing body for addressing zoosanitary and phytosanitary problems, highlighting as a conclusion the need for training of the staff, participated n active, interdisciplinary of human and animal health professionals.
Keywords: Zoonosis; Public Health; zoonosis control programs.